SOCIAL-CULTURAL INFORMAL EDUCATION IN GARDU (POS KAMLING) - Ahmad Nadi (JURNAL SOCIUS, 2022)
Informal education does not only occur in the family environment but also occurs in the community environment and the substation as the media place. The knowledge contained in the community is closely related to social knowledge referring to social relations, meaning that this aspect means that it has existed since humans were born, then the cultural aspect plays a very important role in the educational process, it can be said that there is no education that does not include cultural elements. This study aims to (1) describe social activities at the substation; (2) Describe the socio-cultural informal education at the gardu. The method used in this research is a qualitative method. The data sources were selected by purposive sampling. Observation, interview and documentation techniques were used for data collection. Technical analysis of data using qualitative analysis with data reduction steps, data presentation and drawing conclusions. The results of this study are: (1) Social activities at the gardu are almost the same every day depending on the supporting facilities, such as TV, dominoes, chess and carom boards. (2) Socio-cultural informal education is divided into two, namely the social field (Attitudes and Morals) and the cultural field (Habits, Knowledge and Religion). The conclusion of this study is that the activities that occur at the gardu have informal education for visitors, especially in the social (attitudes and decency) and culture (Habits, Knowledge and Religion) fields. Based on the results of the study, it is hoped that readers will know about informal education that occurs in the community specifically at the substation